A Systematic Review of Calorie Labeling and Modified Calorie Labeling Interventions: Impact on Consumer and Restaurant Behavior. Issue 12 (17th October 2017) - Bleich, Sara N.; Economos, Christina D.; Spiker, Marie L.; Vercammen, Kelsey A.; VanEpps, Eric M.; Block, Jason P.; Elbel, Brian; Story, Mary; Roberto, Christina A.
Abstract : Objective: Evidence on the effects of restaurant calorie labeling on consumer and restaurant behavior is mixed. This paper examined: (1) consumer responses to calorie information alone or compared to modified calorie information and (2) changes in restaurant offerings following or in advance of menu labeling implementation. Methods: Searches were conducted in PubMed, Web of Science, Policy File, and PAIS International to identify restaurant calorie labeling studies through October 1, 2016, that measured calories ordered, consumed, or available for purchase on restaurant menus. The reference lists of calorie labeling articles were also searched. Results: Fifty‐three studies were included: 18 in real‐world restaurants, 9 in cafeterias, and 21 in laboratory or simulation settings. Five examined restaurant offerings. Conclusions: Because of a lack of well‐powered studies with strong designs, the degree to which menu labeling encourages lower‐calorie purchases and whether that translates to a healthier population are unclear. Although there is limited evidence that menu labeling affects calories purchased at fast‐food restaurants, some evidence demonstrates that it lowers calories purchased at certain types of restaurants and in cafeteria settings. The limited data on modified calorie labels find that such labels can encourage lower‐calorie purchases but may not differ in effects relative to calorie labels alone.